Forty-five patient-derived xenografts capture the clinical and biological heterogeneity of Wilms tumor - Andrew J. Murphy (Nature Portfolio, 2019)
The progress in pre-clinical drug discovery for Wilms tumor (WT) is limited by a lack of disease models. Here, the authors develop 45 heterotopic WT patient-derived xenografts including several anaplastic models that recapitulate the biological heterogeneity of WT, and propose this as a resource for evaluating future therapeutics for WT.